Not getting better but not getting worse: A cluster randomized controlled pilot trial of a leadership implementation strategy - Jill Locke; Catherine M. Corbin; Roger Goosey; Vaughan K. Collins; Mark G. Ehrhart; Kurt Hatch; Christine Espeland; Aaron R. Lyon (Implementation Research and Practice)
Background Implementation of evidence-based practices (EBPs) in schools is fraught with challenges. Even when EBPs are initiated, deterioration of implementation efforts often hinders their long-term success. School leadership behaviors can influence teachers’ EBP implementation. Our study tested an implementation strategy called Helping Educational Leaders Mobilize Evidence (HELM), adapted from the Leadership and Organizational Change for Implementation strategy, to enhance EBP implementation through improvements in school leadership teams’ implementation leadership and climate to buffer against the deterioration of implementation efforts. This study explores the impact of HELM on theorized mechanisms of change (i.e., implementation leadership, climate), educator-level factors (i.e., implementation citizenship), and implementation outcomes (i.e., fidelity, initiative stability). Method One school district and 10 schools in Washington participated. Five of the schools were randomized to receive the HELM strategy and the remaining five schools received an alternative leadership training as an implementation attention control. Teachers at every school ( n  = 341) received training for an EBP called Positive Greetings at the Door that has been previously demonstrated to reduce student behavior problems. Principals and Assistant Principals ( n  = 18) received the HELM strategy or alternative leadership training. Three district Administrators also participated in HELM as part of the Organizational Strategy Development meetings. Results HELM significantly slowed the average decline of implementation leadership (perseverant leadership and communication), three dimensions of implementation climate (recognition, rewards, and existing supports) and total implementation climate, and one dimension of implementation citizenship (keeping informed). No significant effects were found with regard to implementation outcomes (i.e., fidelity, initiative stability). Conclusions HELM shows promise in buffering the deterioration of EBP implementation efforts in schools. HELM positively influenced implementation leadership and climate, which are the hypothesized mechanisms for promoting successful long-term implementation efforts. An appropriately powered trial is needed to determine the efficacy of HELM in the future. Name of the registry: clinicaltrials.gov Trial registration number: NCT06340074 Date of registration: March 29, 2024. Retrospectively registered URL of trial registry record: https://clinicaltrials.gov/study/NCT06340074?intr=helm&rank=